A study on theory and practice on enterprise multi businesses - Han, Fengxing (2008)
Systematically sum up the theories and, combining GT’s condition, introduce and analyze the developing course of multi-operation, as well as the evolution from multi-operation to centralization. It will also state the experience of multi-operation and corporate development, research on theories and analysis of sample companies.